Comparative Respiratory Physiology in Cetaceans - Fahlman, Andreas; Borque-Espinosa, Alicia; Facchin, Federico; Fernandez, Diana Ferrero; Caballero, Paola Muñoz; Haulena, Martin; Rocho-Levine, Julie (Frontiers in Physiology, 2020)
In the current study we used breath-by-breath respirometry to evaluate respiratory physiology under voluntary control in a male beluga calf (Delphinapterus leucas, body mass range [Mb]: 151-175 kg), an adult female (estimated Mb = 500-550kg) and a juvenile male (Mb = 279kg) false killer whale (Pseudorca crassidens) housed in managed care. Our results suggest that the measured breathing frequency (fR) is lower, while tidal volume (VT) is significantly greater as compared with allometric predictions from terrestrial mammals. Including previously published data from adult bottlenose dolphin (Tursiops truncatus) beluga, harbour porpoise (Phocoena phocoena), killer whale (Orcinus orca), pilot (Globicephala scammoni), and gray whale (Eschrichtius robustus) show that the allometric mass-exponents for VT and fR are similar to that for terrestrial mammals (VT: 1.00, fR: -0.20). In addition, our results suggest an allometric relationship for respiratory flow Respiratory physiology in cetaceans, with a mass-exponent between 0.63-0.70, and where the expiratory was an average 25% higher as compared with inspiratory flow. These data provide enhanced understanding of the respiratory physiology of cetaceans and are useful to provide proxies of lung function to better understand lung health or physiological limitations.